1966
DOI: 10.1063/1.1754721
|View full text |Cite
|
Sign up to set email alerts
|

EFFICIENT ELECTROLUMINESCENCE FROM GaAs DIODES AT 300°K

Abstract: The light-emitting diodes described in this Letter differ from standard type diodes insofar as the amphoteric dopant Si is the dominant impurity on both sides of the junction. The p-n junction is completely solution regrown. The highly compensated p region gives rise to a wide active region up to 50 μ in width. The interesting feature of these diodes is their high external quantum efficiencies at 300°K. Values up to 6% have been measured on diodes, when an antireflecting coat has been applied.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
28
0

Year Published

1968
1968
2007
2007

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 124 publications
(29 citation statements)
references
References 5 publications
1
28
0
Order By: Relevance
“…As a support for this explanation, Si is known to be incorporated as an acceptor in the liquid phase epitaxy ͑LPE͒ where the growth of a GaAs crystal is carried out in a Ga-rich atmosphere. 33 In a preliminary study by photoluminescence measurements of these Si-doped epilayers, we also found peaks corresponding to Si donors and Si acceptors. At the normal growth temperature of MBE, the growth surface is maintained as an Asstabilized one even if the resulting epilayer is stoichiometric.…”
Section: Discussionmentioning
confidence: 90%
“…As a support for this explanation, Si is known to be incorporated as an acceptor in the liquid phase epitaxy ͑LPE͒ where the growth of a GaAs crystal is carried out in a Ga-rich atmosphere. 33 In a preliminary study by photoluminescence measurements of these Si-doped epilayers, we also found peaks corresponding to Si donors and Si acceptors. At the normal growth temperature of MBE, the growth surface is maintained as an Asstabilized one even if the resulting epilayer is stoichiometric.…”
Section: Discussionmentioning
confidence: 90%
“…The reason for the unusual width of the emitting region is not yet clear. Rupprecht et al 2 explained it in terms of a long electron-diffusion length.…”
Section: Introductionmentioning
confidence: 98%
“…The recombination time r for electrons in the p-region can be derived as a function of the stored charge Q and the forward current I by means of the continuity equation, d1e(x) /dx= e (dn/dt) (1) and recombination kinetics,…”
Section: Discussionmentioning
confidence: 99%